Titanium dioxide nanoparticles induce energy perturbation by stimulating glycolytic metabolic profile in rats - Kehinde, Samuel; Adelesi, Oluwatobi; Ugbaja, Regina Ngozi; Dare, Enock; Ademuyiwa, Oladipo (Life Sciences, Medicine and Biomedicine, 2024)
The safety of titanium dioxide nanoparticles (TiO2-NPs) remains uncertain due to a scarcity of data regarding its absorption, distribution, elimination, and potential adverse effects following oral exposure. As emerging evidence suggests perturbations in energy metabolism play a pivotal role in the toxicity induced by various toxicants, this investigation aimed to assess the effect of TiO2-NPs on the activities of specific glycolytic enzymes in rats. In this study, seventy-two (72) male Wistar rats (200 ± 20g) were divided into 12 groups, each consisting of 6 animals. The rats were orally exposed to TiO2-NPs (8-12nm) at doses of 50, 150, and 250 mg/kg body weight (BW) for durations of 4, 8, and 12 weeks. The control groups received distilled water. The results showed that, except for the 150 mg/kg BW dose of 12 weeks, TiO2-NPs exposure led to an up-regulation in hexokinase activity in lymphocytes, plasma, erythrocytes, and the liver. Hepatic and lymphocyte aldolase activities were also up-regulated, except at 8 and 12 weeks for the 50 and 150 mg/kg BW doses, where slight decreases were observed. Plasma aldolase increased, except at 12 weeks for 150 mg/kg BW dose, while erythrocyte aldolase increased only during the 4 and 8-week exposure but decreased throughout the 12-week exposure. Notably, compared to erythrocyte lactate dehydrogenase activity, which decreased, a consistent pattern observed in lymphocytes, plasma, and hepatic enzymes was a down-regulation at 8 and 12 weeks for the 50 and 150 mg/kg BW doses of TiO2-NPs. In other instances, and time intervals, lactate dehydrogenase was up-regulated. The data from this study underscores that exposure to TiO2-NPs can disrupt the glycolytic pathway of energy metabolism, particularly during the initial 4 weeks of exposure. These perturbations are characterized by increased glycolytic enzymes activity in the lymphocytes, plasma, and the liver.